2016
DOI: 10.1002/smj.2597
|View full text |Cite
|
Sign up to set email alerts
|

How much do CEOs really matter? Reaffirming that the CEO effect is mostly due to chance

Abstract: How much of the variance in firm performance can be attributed to CEOs? This question has been the focus of a long debate in management research. In a recent study, I showed that a large portion of the performance differences that are often attributed to CEOs might in fact be due to chance. In a recent article, Quigley and Graffin argue that my conclusions can be avoided if more advanced methodological approaches are applied. Here I show that this is not the case, in fact if more realistic assumptions of how c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 50 publications
(66 reference statements)
2
73
0
Order By: Relevance
“…In addition, phenomena such as global outsourcing, healthcare management, bribery, corruption, political risks and poverty add to the challenges faced by organizations (Morris et al, 2016). Finally, competitors that possess fresh ideas and market-penetrating techniques make the sustainable competitive advantage of organizations a remote possibility, intensify the role of chance and luck as its likely explanation (Fitza, 2017). To survive in current times and in the future, organizations are required to strategically renew themselves (Ocasio et al, 2018;Pratap and Saha, 2018;Riviere et al, 2018).…”
Section: Strategic Renewalmentioning
confidence: 99%
“…In addition, phenomena such as global outsourcing, healthcare management, bribery, corruption, political risks and poverty add to the challenges faced by organizations (Morris et al, 2016). Finally, competitors that possess fresh ideas and market-penetrating techniques make the sustainable competitive advantage of organizations a remote possibility, intensify the role of chance and luck as its likely explanation (Fitza, 2017). To survive in current times and in the future, organizations are required to strategically renew themselves (Ocasio et al, 2018;Pratap and Saha, 2018;Riviere et al, 2018).…”
Section: Strategic Renewalmentioning
confidence: 99%
“…Thus, it is critical for scholars to pinpoint essential strategic leadership behaviours or practices that will lead to high levels of performance (Mutia 2015; Jansen et al, 2009; Jouste & Fourie 2009). Unfortunately, due to inertial forces in the form of organizational and other environmental constraints, some studies have demonstrated that on average, strategic leadership has limited leverage on performance (Fitza, 2017;Hambrick & Quigley, 2014). A possible explanation for these empirical gaps could be how strategic leadership and performance have been conceptualized and measured and the probable intermediate effects of the moderating and mediating variables.…”
Section: Strategic Leadershipmentioning
confidence: 99%
“…Empirical studies have demonstrated that strategic leadership is an important determinant of organizational performance (Witts, 2016; Lord, et al, 2016). However, other studies assert that strategic leadership is an inconsequential determinant of performance because of various constraints they face or due to some randomness or chance effects (Fitza, 2017;Quigley & Hambrick, 2015;Day & Lord, 1988). A further explanation of these empirical gaps could be how the constructs of strategic leadership is operationalized and measured and the difficulty in identifying a way of integrating the complex and multi dimensionality nature of performance.…”
Section: Organizational Performancementioning
confidence: 99%
See 2 more Smart Citations